Bangladesh - Orr, Tamra (Enchantment of the world., 2019)
Though it is only about the size of Iowa, Bangladesh is one of the world's most populous countries. It has faced many difficulties, but it is rich in history and culture. Readers will explore the nation's beautiful landscapes and densely-packed cities as they find out how the country was first settled and how it has changed over time. They will also learn about Bangladesh's government, its economy, and much more.